Work Related Musculoskeletal Disorders in Electrical, Telecommunication and Instrument Mechanics of Armed forces - Roli, Dave; Ali, Irani; Neekhra, Vikram (International Journal of Occupational Safety and Health, 2020)
Background: Modern defence system has a significant role of electrical, electronic and instrument technicians in armed forces. Despite their intensive role, little is known about work-related musculoskeletal disorder in these technicians. Objective: To investigate the prevalence of the work-related musculoskeletal disorder in defence personnel involved in electrical and electronic maintenance and repairs. Methods: A cross-sectional study was carried out for 3 years, in Electrical, telecom and instrument defence technicians (N = 164). Prevalence of work-related musculoskeletal disorder was assessed using the Nordic Musculoskeletal Questionnaire. Effect of age, working hours, work experience, Basal metabolic index and type of job on the prevalence of work-related musculoskeletal disorder was investigated using logistic regression analysis. Results: A total of 119 (72.56%) respondents reported work-related musculoskeletal disorder with 53.04% multiples & 19.51% single work-related musculoskeletal disorder. Simultaneous presence of neck, shoulder and upper back work-related musculoskeletal disorder were observed. Highest rate of work-related musculoskeletal disorder was in neck (44.44%), followed by shoulder (27.16%), ankle/ foot (14.81%), elbow/ forearm (12.96%), low back (11.72%) and wrist/ finger (9.87%). Neck (44%) related work-related musculoskeletal disorder were highest across all job crafts. Work experience (p = 0.012; OR = 0.87; 95% CI – 0.78- 0.97), working hours (p = 0.031; OR= 1.73, 95% CI – 0.58-5.12) smoking (p = 0.00 ; OR = 5.3, 95 % CI = 4.3 – 8.48) and job crafts like electrician (p = 0.434; OR = 1.89, 95% CI = 1.08-3.31) and telecom mechanics (p = 0.026; OR = 1.26, 95% CI =0.74 – 2.15) were significantly associated as risk factors of work-related musculoskeletal disorder. Conclusion: High prevalence of work-related musculoskeletal disorder was observed in electrical, telecommunication & instrument mechanics, with higher multiple work-related musculoskeletal disorder. Working hours, work experience, job craft and smoking were highly associated with a work-related musculoskeletal disorder. We suggest suitable ergonomic intervention and awareness program along with smoking control drive to reduce the risk of work-related musculoskeletal disorder.